2015
DOI: 10.1177/1049731515588597
|View full text |Cite
|
Sign up to set email alerts
|

Recovery From Schizophrenia in Community-Based Psychosocial Rehabilitation Settings

Abstract: Objective: We assessed the rate of recovery from schizophrenia in community-based psychosocial rehabilitation and whether psychosocial attributes predicted the achievement of recovery beyond demographic and clinical characteristics. Methods: We used data from 246 individuals with schizophrenia spectrum disorder collected at baseline and at 6 and 12 months after admission to psychosocial rehabilitation. Results: The proportion of participants who showed recovery during either 6-month period and the full 1-year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 77 publications
1
11
1
5
Order By: Relevance
“…The corresponding categories and the themes derived are presented in Table 1. Table 2 above indicated an overview of the participants' demographics, which reveals the number of males was seventeen (17), and twelve (12) females, which is consistent with the fact there are more men living with schizophrenia than women, as declared by Lim (2017). This is also consistent with the declaration of Seeman (2018) who's review study discovered schizophrenia was more common in men than women, with the reason that male and female DNA is exposed to different environmental input which differentiates level of predisposition to schizophrenia.…”
Section: Trustworthinesssupporting
confidence: 58%
“…The corresponding categories and the themes derived are presented in Table 1. Table 2 above indicated an overview of the participants' demographics, which reveals the number of males was seventeen (17), and twelve (12) females, which is consistent with the fact there are more men living with schizophrenia than women, as declared by Lim (2017). This is also consistent with the declaration of Seeman (2018) who's review study discovered schizophrenia was more common in men than women, with the reason that male and female DNA is exposed to different environmental input which differentiates level of predisposition to schizophrenia.…”
Section: Trustworthinesssupporting
confidence: 58%
“…The current study included a large sample of community-dwelling patients with schizophrenia to explore the relationships between global function, empowerment, and recovery. Converting the scale used herein into a percentage shows an empowerment level of 55.4% and a recovery level of 69.1%, which are slightly higher than those presented in other studies [10,19]. This may have been related to differences in the research populations considering that the current study included participants who availed of various community care services, such as outpatient clinics, day wards, or home treatment services, and excluded those not receiving community care services.…”
Section: Discussionmentioning
confidence: 65%
“…Psychiatric consumers de ne recovery as the attainment of a meaningful and valued life rather than the absence of symptoms. Studies have also shown that recovery can be a care outcome [10][11][12]. Notably, global mental health care aims to improve recovery, with developed countries already having successfully developed related recovery programs and effectiveness evaluations [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative outcome research in other psychosocial services has viewed people who spend years in vocational programmes without moving on to paid employment, as struggling to recover. 11 , 36 Such studies highlight the importance of how recovery is conceptualised by research. Quantitative studies generally assume an outcomes-focused approach that differentiates between social recovery, including employment and interpersonal outcomes, and complete recovery, focused on symptom reduction.…”
Section: Discussionmentioning
confidence: 99%